Anticancer activity of two ruthenium(II) polypyridyl complexes toward Hepatocellular carcinoma HepG-2 cells. (1st September 2019) - Jiang, Guang-Bin; Zhang, Wen-Yao; He, Miao; Gu, Yi-Ying; Bai, Lan; Wang, Yang-Jie; Yi, Qiao-Yan; Du, Fan
Graphical abstract: Two new Ru(II) polypyridyl complexes were synthesized and characterization. DNA-binding behaviors of the complexes were investigated. Most importantly, the further anticancer mechanism of the Ru(II) complexes was explored by apoptosis, cell invasion, intracellular reactive oxygen species (ROS) levels and mitochondrial membrane potentials. Abstract: Two novel ruthenium(II) polypyridyl complexes [Ru(bpy)2 (ETPIP)](ClO4 )2 (Ru(II)-1 ) and [Ru(phen)2 (ETPIP)](ClO4 )2 (Ru(II)-2 ) (bpy = 2, 2 ′ -bipyridine, ETPIP = 2-(4-(thiophen-2-ylethynyl)phenyl)-1 H -imidazo[4, 5- f ][1, 10]phenanthroline, phen = 1, 10-phenanthroline) have been synthesized and characterized. The DNA binding behaviors were evaluated using electronic absorption titration, luminescence spectra and viscosity measurement, revealing an intercalative mode. The cytotoxicity of the ligand and Ru(II) complexes toward A549, HepG-2, SGC-7901 and Hela was assayed by MTT ((3-(4, 5-dimethylthiazo-2-yl)-2, 5-diphenyltetrazolium bromide)) method. Notably, ETPIP shows no anticancer activity against selected cell lines, and complexesRu(II)-1 (IC50  = 18.4 ± 2.1 μM) andRu(II)-2 (IC50  = 16.5 ± 1.7 μM) were found to be slightly more effective against HepG-2 cells than cisplatin (IC50  = 26.4 ± 2.6 μM). Evaluation of cell invasion was performed with the Boyden chamber invasion assay. Additionally, the cell cycle distribution of HepG-2 cells was carried out by flow cytometry. Most importantly, the further anticancer mechanism of the Ru(II) complexes was explored by apoptosis, intracellular reactive oxygen species (ROS) levels and mitochondrial membrane potentials. These results reveal that complexesRu(II)-1 andRu(II)-2 could induce apoptosis in HepG-2 cells via a ROS-mediated mitochondrial dysfunction pathway.